2020
DOI: 10.1039/d0cp00433b
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural dependent oxygen reduction reaction in a Ruddlesden–Popper perovskite (SmSr)NiO4−δ

Abstract: Alteration in conduction pathways through Microstructural difference:Microstructural designing for Ruddlesen–Popper structured layered perovskite, (SmSr)NiO4−δ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is observed that CR is lower for x = 0.6 (B0.0033 mm per year) than that for x = 1.0 (B0.029 mm per year) (insets (a) and (b)). Earlier, 43 we have observed lower CR for the sample x = 1.0, which might be due to the different concentration of analytes. The different CR corresponds to the different passivation mechanism and different thicknesses of protective films developed over the cathode leading to a decrease in peak current.…”
Section: Thin Filmmentioning
confidence: 43%
See 1 more Smart Citation
“…It is observed that CR is lower for x = 0.6 (B0.0033 mm per year) than that for x = 1.0 (B0.029 mm per year) (insets (a) and (b)). Earlier, 43 we have observed lower CR for the sample x = 1.0, which might be due to the different concentration of analytes. The different CR corresponds to the different passivation mechanism and different thicknesses of protective films developed over the cathode leading to a decrease in peak current.…”
Section: Thin Filmmentioning
confidence: 43%
“…3.3 Catalysis studies 3.3.1 Bulk. In our recent studies, 43 we have observed the effect of microstructures on the triple-phase boundary and the change in the number of electron transfer from 2e À to 4e À in SmSrNiO 4Àd (i.e., x = 1.0) with the sintering temperature from 1250 1C to 1425 1C. The electrocatalysis is believed to be affected with the structure change, and we have studied the electrocatalysis for all the studied samples (see Fig.…”
Section: Thermogravimetric Studiesmentioning
confidence: 98%